Bronchospasm during general anaesthesia-an alarming threat - Ali, Md Rashid; Mojibuddin, -; Adom, Shamim; Khatun, Rahena; Khan, KR; Paul, Debashish (KYAMC Journal, 2018)
Bronchospasm and wheezing are not synonymous terms. Bronchospasm is only one cause of wheezing and before the diagnosis can be made, the other causes of wheezing must be excluded. Cyanosis may occasionally be the first sign of severe bronchospasm. An anaesthetist must be alert to diagnose such a case promptly and immediate treatment should be started. Confirmation of diagnosis is not simply a matter of detecting wheezing on auscultation of the chest. It is equally possible to hear no wheezes in the presence of severe bronchospasm, as a result of minimal air movement. Urgent management of such a case includes, Oxygenation, Steroids, Bronchodilators, Lignocaine, Inhalational Anaesthetic agents and other supportive drugs. Close monitoring must be ensured. KYAMC Journal Vol. 8, No.-2, Jan 2018, Page 27-30